INFRASTRUKTUR JARINGAN KOMPUTER BERBASIS CISCO PACKET TRACER DI LABKOM UNIVERSITAS MUHAMMADIYAH SUKABUMI - Afwa, Nafilah; Dadan Rahmat (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2025)
Computer network technology plays a crucial role in supporting teaching and learning activities. A Local Area Network (LAN) is a type of computer network that connects devices within a specific area. The application of network technology supports the learning process, including in the Computer Laboratory of the Information Technology Education Program. This research aims to design and configure the computer network infrastructure in the laboratory using wired media. The method used is the Network Development Life Cycle (NDLC), which relies on previous development processes. The research methodology involves simulation with Cisco Packet Tracer to design network topology and configure devices. The research results include the design of computer network infrastructure using wired media and optimal IP configuration. Findings indicate that the devices within the designed network topology are interconnected and can access the internet effectively.